Early Childhood Education And Village Corruption: An Evidence From Indonesia - Anggun Nurjannah (Eduvest - Journal of Universal Studies, 2024)
This study explores the relationship between early childhood education (ECE) exposure and corruptive behavior among village leaders in Indonesia, particularly in light of the decentralization efforts that began in 2014 with the Village Fund Initiative. The objective is to determine whether village leaders who were exposed to ECE in their early years are less prone to engage in corrupt practices when managing public funds. The research utilizes a staggered difference-in-difference approach, comparing corruption cases between leaders exposed to ECE and those who were not. The study collected data from the Indonesian village census (PODES) between 1993 and 2018, focusing on Java Island. The corruption cases were sourced from the Indonesian Supreme Court, specifically analyzing the behavior of village heads elected post-2014. The methodology allowed for a quasi-experimental design by leveraging the timing of village elections as a key variable. The results ECE exposure did not universally reduce corruption across the sample. In fact, corruption surged among early-treated groups who experienced the program in the 1990s, suggesting that ECE alone is not a strong deterrent to corruption. However, for later-treated groups, ECE exposure did lead to a reduction in corrupt behavior, pointing to an adaptation effect as village leaders observed peers being prosecuted for corruption. In conclusion, while early childhood education plays a role in shaping governance outcomes, its impact on reducing corruption is nuanced. The findings suggest that integrating anti-corruption education into the ECE curriculum could strengthen governance at the village level, particularly when combined with robust law enforcement mechanisms